Stakeholder priorities for inclusive accessible housing: a systematic review and multicriteria decision analysis - Lakhani, Ali; Zeeman, Heidi; Wright, Courtney J.; Walting, David P.; Smith, Dianne; Islam, Rafikul (John Wiley and Sons Ltd, 2020)
from an Australian Research Council funded study where the analytic hierarchy process (AHP) was utilized to compare and contrast inclusive housing development priorities among relevant stakeholders. A multistage process was undertaken to ascertain the AHP criteria for inclusive housing development decisions, including a systematic review of peer‐reviewed and grey literature, in addition to a structured focus group with end users (n = 17) and an industry stakeholder online survey (n = 130). Finally, a subgroup of industry stakeholders (n = 29) representing the housing, health, and disability sectors completed the AHP to establish decision priorities. The final AHP model indicated three broad clusters of decision priorities for inclusive accessible housing development: end‐user connectedness, building considerations, and feasibility, respectively. Global weights conclude that specific end‐user connectedness elements, namely, “access to health care,” “community engagement,” “proximity to transport,” and “security and safety,” were the foremost priorities. It is expected that inclusive housing development decisions that integrate the connectedness of end users first and foremost, with building and feasibility priorities, will favourably impact the housing opportunities and choices for people with disability.